UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG ANAK MELALUI MEDIA ULAR TANGGA DI TK MUSLIMAT NU 1 PAMEKASAN - Yulistiawati; Khairunisa; Mediyana; Humairoh, Annisatul; Mufarrohah, Vina; Aini; Farida; Tur’ah, Siti (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
This research aims to help Muslimat NU 1 Kindergarten students become more proficient in counting with the media used, namely the snakes and ladders game. The method of this research is Classroom Action Research (PTK), this research consists of two cycles which have planning, implementation, observation and reflection stages, for children from group B of the Muslimat NU 1 Pamekasan Kindergarten, totaling 19 children. data is collected through observation, arithmetic ability tests, andfield notes.The research results obtained when using the snakes and ladders game were a significant increase in children's numeracy skills. in the first cycle, the increase in numeracy ability reached 36.8%, and in the second cycle it increased to 63.1%. snakes and ladders media can influence children to be more active, enthusiastic and motivated when learning to count through fun and interactive games. Thus, using snakes and ladders media has proven to be effective in improving the numeracy skills of young children at the Muslimat NU 1 Pamekasan Kindergarten